PENDIDIKAN KEWARGANEGARAAN SEBAGAI SARANA PENGEMBANGAN KEPEMIMPINAN - Suci Hamida Tunil Khayra; Syamzaimar Syamzaimar (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
In the era of digital disruption and globalization, Indonesia faces a leadership crisis that demands strong character education, with Citizenship Education (Civic Education/PKn) serving as a strategic means for developing integrity-based Pancasila leadership. This study aims to analyze how PKn materials and methods transform students into adaptive leaders through qualitative descriptive literature review. Data were collected from 18 scientific journals and 2 books from the 2021-2026 period via Google Scholar, SINTA, and university repositories, analyzed using thematic content analysis technique (open-axial-selective coding). The synthesis results reveal that PKn effectively develops leadership through three dimensions: cognitive (constitutional understanding), affective (democratic empathy), and conative (OSIS/PMII practice). Project-based learning and teachers' servant leadership enhance soft skills by 40-60%, particularly in the Merdeka Curriculum. PKn functions as an incubator for prophetic leadership in Society 5.0, with main themes of Pancasila inculcation, active learning, and extracurricular collaboration. It is concluded that PKn proven as a transformational means of holistic leadership for Indonesia Gold 2045. Recommendations include AI/VR integration, transformational teacher training, and longitudinal mixed methods research. This study fills the post-pandemic literature gap regarding the long-term impact of PKn on the national leadership generation.